Using the ARDL Approach to Investigate the Nexus Between Financial Risk and Sukuk Market Development - Roslen, Siti Nurhidayah Mohd; Zaghlol, Azlul Kalilah; Abdul Aziz, Muhammad Ridzuan (Journal of Entrepreneurship, Business and Economics; Vol 10 No 2S1 (2022): Theme: Promoting Financial and Household Resilience, 2022)
The purpose of this paper is to examine the effect of financial risk factors on Sukuk market development in Malaysia during the period 2015 to year 2021. To capture the effect of financial risk factors on Sukuk market development, the authors estimated the long-run linkage by using ARDL bounds testing approach to cointegration. This study confirmed the existence of both long-run and short-run relationships between the financial risk factors and Sukuk market development. The authors also found that the coefficient for international liquidity stability is positive and statistically significant in the long-run, but negative and statistically significant in the short-run. Findings obtained in this research can further justify the premium price to be paid in purchasing Sukuk as compared to conventional bond which may be beneficial to Sukuk market players in understanding these securities better in capitalizing its benefit to portfolio diversification. The use of ARDL approach that examines the long-run and short-run effects of financial risk factors on Sukuk market development in Malaysia makes the current study value added to the literature since there is scant research conducted in the same area using samples from an emerging Asian market. Research paper Keywords: Financial risk, Sukuk, ARDL model, Mala ysia market Reference to this paper should be made as follows: Roslen, S. N. M, Zaghlol, A. K., & Abdul Aziz, M. R. (2022). Using the ARDL Approach to Investigate the Nexus Between Financial Risk and Sukuk Market Development. Journal of Entrepreneurship, Business and Economics , 10 (2S1), 95–123.